Int J Depress Anxiety 2018
DOI: 10.23937/ijda-2017/1710008
|View full text |Cite
|
Sign up to set email alerts
|

State and Trait Anxiety Evaluation in Dental Patients

Abstract: The purpose of this study was to evaluate the possible relation between dental patient's state anxiety, demographic factors and past experience of treatments with their trait anxiety in patients undergoing root canal treatments (RCT).Materials and Methods: 60 patients participated in this study. A single molar was treated in every patient. At their first visit, patients were asked to fill out a questionnaire about their demographic and educational status as well as a Persian version of STAI-T (Spielberger Trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…In the present study, the average maternal age was about 40, and it is possible that these were mature women capable of coping with life challenges and crises, which enabled them to cope with the Covid-19 more optimally. Similarly, the findings of the present study are consistent with other research reporting a lack of association between education and SA (e.g., Razavian et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the average maternal age was about 40, and it is possible that these were mature women capable of coping with life challenges and crises, which enabled them to cope with the Covid-19 more optimally. Similarly, the findings of the present study are consistent with other research reporting a lack of association between education and SA (e.g., Razavian et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, studies have indicated a lack of correlation between education and SA (e.g., Razavian et al, 2018). Despite the lack of uniformity in findings and given the multiplicity of studies showing the opposite picture, evidence suggests that single mothers are more likely to report higher stress than married mothers (Cairney et al, 2003)—for example, SMBC might report lower mental health and quality of life than married mothers.…”
Section: Introductionmentioning
confidence: 99%